2015
DOI: 10.3892/ijo.2015.3163
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of CCAAT enhancer binding protein α P42 induces myeloid differentiation and overcomes all-trans retinoic acid resistance in human acute promyelocytic leukemia NB4-R1 cells

Abstract: All-trans retinoic acid (ATRA) is one of the first line agents in differentiation therapy for acute promyelocytic leukemia (APL). However, drug resistance is a major problem influencing the efficacy of ATRA. Identification of mechanisms of ATRA resistance are urgenly needed. In the present study, we found that expression of C/EBPα, an important transcription factor for myeloid differentiation, was significantly suppressed in ATRA resistant APL cell line NB4-R1 compared with ATRA sensitive NB4 cells. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…At high concentrations of GM-CSF, C/EBP increases quickly, resulting in a swift rise in Gfi-1 and repression of PU.1, thereby inducing granulopoiesis. The result, that C/EBP is an antagonist of PU.1 in granulopoiesis, is in agreement with Wang et al ( 84 ), who showed that induction of an isoform of C/EBPα downregulates the SPI1 gene (encoding PU.1) to promote granulopoiesis. Alternatively, our model predicts that C/EBP has a positive impact on PU.1 in GM-CSF induced monopoiesis, as a result of a slower increase in C/EBP, allowing PU.1 enough time to upregulate itself and establish dominance.…”
Section: Discussionsupporting
confidence: 92%
“…At high concentrations of GM-CSF, C/EBP increases quickly, resulting in a swift rise in Gfi-1 and repression of PU.1, thereby inducing granulopoiesis. The result, that C/EBP is an antagonist of PU.1 in granulopoiesis, is in agreement with Wang et al ( 84 ), who showed that induction of an isoform of C/EBPα downregulates the SPI1 gene (encoding PU.1) to promote granulopoiesis. Alternatively, our model predicts that C/EBP has a positive impact on PU.1 in GM-CSF induced monopoiesis, as a result of a slower increase in C/EBP, allowing PU.1 enough time to upregulate itself and establish dominance.…”
Section: Discussionsupporting
confidence: 92%
“…The C-terminal Myc-DDK-tagged pLenti plasmid carrying the full-length Homo sapiens NR3C1 coding sequence ( NR3C1 , 2334 bp, NM_000176; hereafter called pLenti-C-Myc-DDK-NR3C1) was purchased from Biowestern Technologies (Hangzhou, China). Detailed methods for lentivirus infection have been described previously [4]. In brief, lentivirus was produced by cotransfection of packaging plasmids (PSPAX2 and PMD2.G) and lentivirus vectors into HEK293T cells using Attractene Transfection Reagent (Qiagen, Valencia, CA, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…RT-qPCR and western blotting analyses were carried out as previously described [4] with NR3C1 primers 5′-ATAGCTCTGTTCCAGACTCAACT-3′ (forward) and 5′-TCCTGAAACCTGGTATTGCCT-3′ (reverse). GAPDH primers were 5′-ACAACTTTGGTATCGTGGAAGG-3′ (forward) and 5′-GCCATCACGCCACAGTTTC-3′ (reverse).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, further studies are required to illustrate the molecular mechanisms in APL and identify novel factors that regulate differentiation and apoptosis. NB4-R1 cells are naturally resistant to ATRA but sensitive to As 2 o 3 , thus this cell line is a useful model for the study of drug resistance and apoptosis (28,29). Through protein spectrum analysis, the present study identified that the expression of a number of proteins was significantly increased in NB4-R1 cells, a retinoid-resistant cell line, compared with that in NB4 cells, a retinoid-sensitive cell line.…”
Section: Discussionmentioning
confidence: 99%